Simultaneous debut of spontaneous intestinal perforation in a pair of preterm monozygotic twins assessed by whole genome sequencing - Nikolai Juul; Oliver Willacy; Mathilde Maagaard; Tina Olsen; Jakob Ek; Inge Ifaoui; Magdalena Fossum (Elsevier, 2022)
Spontaneous intestinal perforation, although rare, involves high morbidity and mortality in neonates. The etiology of the condition is to this day largely unknown. Here, we present a case of monochorionic preterm twins with synchronized spontaneous intestinal perforation, and the results from whole-genome sequencing to assess possible associations to known genetic diseases. We also discuss other publications related to the etiology of spontaneous intestinal performation or necrotizing enterocolitis in newborn premature children.